2005
DOI: 10.2223/1345
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cystic fibrosis screening program in the state of Paraná: evaluation 30 months after implementation

Abstract: Neonatal screening for cystic fibrosis in the State of Paraná, in accordance with Health Ministry directives, was a pioneering initiative for Brazil. Many patients were diagnosed early, even asymptomatic ones, which is a challenge to improving prognosis with this fatal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
3
1
2
Order By: Relevance
“…The frequency of CF in the present population was one in 6,675 screened newborns, a slightly higher value than that reported in a pilot study at this same center (1:8,403) involving a smaller number of babies and those reported for other Brazilian states (Paraná 1:9,520, Santa Catarina 1:8,776; Minas Gerais: 1:9,115) 22,23,24 .…”
Section: Discussioncontrasting
confidence: 65%
“…The frequency of CF in the present population was one in 6,675 screened newborns, a slightly higher value than that reported in a pilot study at this same center (1:8,403) involving a smaller number of babies and those reported for other Brazilian states (Paraná 1:9,520, Santa Catarina 1:8,776; Minas Gerais: 1:9,115) 22,23,24 .…”
Section: Discussioncontrasting
confidence: 65%
“…In many parts of Latin America, significant progress has been made over recent years in the timely diagnosis of CF. This progress has been achieved through the implementation of pioneering neonatal screening programs (such as those in Brazil, Argentina and Mexico), dedicated CF awareness and training initiatives and increased access and use of molecular and other diagnostic tests [2,[6][7][8][9].…”
Section: Diagnosis and Screeningmentioning
confidence: 99%
“…One group of authors described cases of false-negative newborn screening results despite the use of CFTR gene analysis as a screening strategy. 5 In a study evaluating the newborn screening program in the state of Paraná, Brazil, 30 months after its implementation, 11 only one case of a false-negative newborn screening result was found. In a study involving two centers for CF newborn screening in the state of São Paulo, Brazil, no false-negative results were found over a period of nearly two years.…”
Section: To the Editormentioning
confidence: 99%